The relationship of smartphone addiction with depression, obsession-compulsion, impulsivity, alexithymia among medical faculty students - Özen, Seçil; Topcu, Merve (Journal of Dependence, 2017)
Objective: The purpose of current study is to examine the relationship of smartphone addiction (SA) with depression, obsessivecompulsive symptoms (OCS), impulsivity and alexithymia among medical faculty students. Method: A total of 345 medical faculty students who reported smartphone use enrolled in study. Thirty five students who did not fully fill out the questionnaires excluded. Participants completed sociodemographic information form, Smartphone Addiction Scale (SAS), 20-item Toronto Alexithymia Scale (TAS-20), Short Form of Barratt Impulsiveness Scale (BIS-11-SF), and depression and obsessive-compulsive subscales of Symptom Checklist-90 Revised (SCL-90-R) online. Results: As 57.1 % of participants (n=177) are female, 42.9 % of them are male (n=133). Mean of age was 22.40 (SD=±2.40). SA has significantly positive relationship with depression (r=0.351), OCS (r=0.291), difficulty in identifying feelings (r=0.453), impulsivity (r=0.451), difficulty in describing feelings (r=0.860) and alexithymia total (r=0.688). Moreover results of three-stepped Hierarchical regression analysis revealed that depression significantly predicted SA (p<0.001). In the second step, both depression (p<0.05) and impulsivity (p<0.001) significantly predicted SA. In the last step of regression equation, model comprising of impulsivity (p<0.001), difficulty in identifyingfeelings (p<0.05) and difficulty in describing feelings (p<0.001) and externally oriented thinking (p<0.05) significantly predicted SA. Conclusion: Prominent finding of current study is that although impulsivity and alexith-ymia have been known close to behavioral addictions, even when depression and OCS were controlled, still they were significant and unique predictors of SA. No matter time and place do smartphones serve availability to features like online gaming and connecting social media beside speaking on the phone and messaging. Therefore, availability of and accessibility to smartphone may be a risk factor for addiction. When merging of properties of smartphones and personality features like impulsivity and alexithymia may yield SA in young adults.